2014
DOI: 10.1097/aln.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Steroid Injections, Conservative Treatment, or Combination Treatment for Cervical Radicular Pain

Abstract: For the primary outcome measure, no significant differences were found between treatments, although combination therapy provided better improvement than stand-alone treatment on some measures. Whereas these results suggest an interdisciplinary approach to neck pain may improve outcomes, confirmatory studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 55 publications
0
57
2
1
Order By: Relevance
“…Even the group that received a combination of conservative treatment and epidural injection did not reach a significant level of difference. The scores for arm pain only reduced 1.8, 2.0, and 3.1 points from pretreatment baseline at 1-month follow-up, and the scores for neck pain only reduced 1.1, 1.2, and 2.2 for the 3 groups, respectively [28]. In contrast, the approach used in this study achieved more than 4 points pain score reduction at 1 and 3 months after the procedure.…”
Section: Discussioncontrasting
confidence: 70%
“…Even the group that received a combination of conservative treatment and epidural injection did not reach a significant level of difference. The scores for arm pain only reduced 1.8, 2.0, and 3.1 points from pretreatment baseline at 1-month follow-up, and the scores for neck pain only reduced 1.1, 1.2, and 2.2 for the 3 groups, respectively [28]. In contrast, the approach used in this study achieved more than 4 points pain score reduction at 1 and 3 months after the procedure.…”
Section: Discussioncontrasting
confidence: 70%
“…study comparing a series of epidural steroid injections, medications and physical therapy, and combination therapy for cervical radiculopathy found that a multimodal treatment approach was more effective than stand-alone therapy. 61 Important "core" outcomes of anxiety and depression in addition to satisfaction with treatment also should be included as end points. The primary outcome should be measured at a range of intervals after the intervention.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…A positive predefined successful outcome was considered to be a 2-point reduction in neck pain (or arm pain if worse than neck pain) coupled with a satisfaction score of 4 or greater. 25 …”
Section: Treatment Follow-up Data Collection and Outcomementioning
confidence: 99%